Evaluation of Free-Living Nematode Panagrellus Redivivus as a Live Food Organism for Silver Barb Barbodes Gonionotus Larvae - Jahangard, AbdolSamad (2003)
A series of experiments were conducted to develop mass production and improve nutritional quality of free-living nematode Panagrellus redivivus. The performance of nematodes P. redivivus produced on different culture media on growth and survival of silver barb Barbodes gonionotus larvae were also studied. Prior to evaluation of P. redivivus as a larval live food organism, a study was conducted on the optimal stocking density of B. gonionotus larvae. Best larval growth and survival were obtained at 10 larvae L-1 for a 16-days rearing period. However, a range of 34-65 larvae L-1 was recommended for its commercial hatchery production. A comparative study on performance of nematode, rotifer, Moina and Artemia was carried out. B. gonionotus larvae fed with Artemia and nematode exhibited significantly (P<O.05) highest growth followed by those fed with rotifer and Moina respectively. P. redivivus was found to be a suitable food for B. gonionotus. A following study indicated that 20 nematodes mL-1 was the optimal feeding density for silver barb B. gonionotus stocked at 1 0 larvae L-1 for a 16-days culture period. The study also revealed that 8% starch is the optimal level for the maximum production of P. redivivus. Nematodes produced at 8 % starch also gave the best growth and survival of silver barb larvae. A following study showed that the total production of free-living nematode P. redivivus was significantly affected by the source of starch in culture medium. Potato starch was the best starch for culture of P. redivivus. Starch sources, however, did not have any significant (P>O.05) effect on the biochemical composition and nutritional value of P. redivivus for silver barb P. gonionotus larvae. Another study was conducted to determine the effect of lipid enrichment on the production of P. redivivus. The results showed that the best lipid enrichment level for the maximum production of P. redivivus was 3.43%. The extremely low production of P. redivivus in unenriched medium suggested that lipid has an important role in reproduction, metabolism and as the main energy source. The results of a feeding trial showed that nematodes grown in media enriched with> 2.6% oil level were unsuitable for silver barb B. gonionotus larvae.